AN ANNOTATED TRANSLATION OF PERSONAL PRONOUNS IN THE NOVEL THE SINS OF FATHER - Handayani, Chintia (Universitas Gunadarma, 2019)
This article is based on annotated translation. Annotated translation is a translation with commentary. The objective of this article is to find out strategies that was employed in translating in Personal Pronoun I and You in the novel The Sins of Father by Jeffry Archer. The research used qualitative method with retrospective and introspective as research approached. The syntactic strategies by Chesterman is employ as tools of analysis. The result shows that from 25 data, there are 5 primary data which are taken using purposive sampling technique. There are 3 word ‘I’ and 2 word ‘You’, which all the data has the same translation principle and strategies.